Crossed fused renal ectopia: a report of twelve cases at a tertiary health centre and literature review - Reddy, Suraj Jayadeva; Shah, Milap J.; Reddy, Bathi Sourabh; Chawla, Arun; Singh, Anshuman; Reddy, Bommireddy V. (International Journal of Research in Medical Sciences, 2022)
Crossed fused renal ectopia (CFRE), second most common renal fusion anomaly of the kidney. These patients were mostly asymptomatic and present with complaints due to associated conditions. The management of these conditions was complicated not only by the approach to be picked, but also by the investigation to be performed. The following study was done at a tertiary care centre, with the duration of this study being from January 2019 to April 2021. A total of twelve patients with CFRE required surgical intervention for their symptoms during this period. As a routine history, routine investigations and ultrasound (US) of the abdomen and pelvis was followed for all the patients. Other imaging modalities were opted on case to case basis. Out of n=12 patients of CFRE with fusion who underwent surgical intervention, majority were male patients (n=10). The most common symptom was abdominal pain (n=9). The most common crossed renal ectopia was the left to right fusion (n=7), as compared to right to left CRE (n=5). The most common fusion anomaly was L-shaped (n=8). The endourological procedures (n=6), laparoscopic procedures (n=2) while open procedures (n=4). It is important for a urologist to bear in mind the various presentations of this less known anomaly with diverse presentations. We have highlighted the investigations used at our center which would help plan further treatment and surgical approach in such patient in view of complex renal as well as vascular anatomy.